Android Application for Managing Urgent Convalescent Plasma Blood Request for Covid19 Treatment - Olid, Nasir; Deshinta, Arrova Dewi (INTI International University, 2022)
The emergence of the covid19 pandemic has forced many countries to be more focused on the technologies that can save human life. A lot of efforts have focused on containment and mitigation actions with varying degrees of success. However, lack of attention given to administering urgent requests for convalescent plasma blood as part of treatment for critical covid19 patients although the passive administration of antibodies from a person who has convalesced may be an effective therapy for those patients who have yet to develop their antibody response. Hence, interest in the use of convalescent plasma has been rising, not only commenced by medical professionals but also among patients’ family members, especially for urgent requests. This paper proposed timeline-based posts to tackle the urgent-request issue that sort based on first come first serve priority. From this timeline, the people in search of donors may find donors’ information and location quickly. Furthermore, we added a timeline page, search function, a virtual assistant (chatbot) that automatically shares posts to social media without exiting the app, etc. These features promote the hit to the right users and their respond faster than before. The previous study reported from the 40 PSARS patients undergoing ribavirin and methylprednisolone treatment, 19 were administered with convalescent plasma, whereas 21 were given an additional dose of methylprednisolone. The group of patients who were treated with plasma therapy showed better recovery and reduced mortality. With this situation, we hope our contribution in the form of an Android app can assist those in need at the right time and save more lives. Moreover, this app can be referred to as a model for other comparable apps.